The accountability paradox in an age of reinvention: the perennial problem of preserving character and judgment - Jos, Philip H.; Tompkins, Mark E. (2004)
The rapidly expanding literature on accountability reveals a centrally important paradox: Responsible interpretation and application of external accountability demands depends on the cultivation of the virtues that support good administrative judgment, but the institutions and mechanisms that are used to communicate these external standards, and that monitor compliance with them, often threaten the very qualities that support responsible judgment. Consulting a rich and varied literature, this paradox is explored as it emerges in both the more familiar compliance-based accountability processes and the less well-understood performance-based processes associated with reinvention and the new public management. - Reproduced.
Keywords: Accountability